Environmental Justice Organizing for Environmental Health: Case Study on Asthma and Diesel Exhaust in Roxbury, Massachusetts. - Loh, Penn.; Sugerman-Brozan, Jodi. (Tufts University. Tisch Library., 2019)
This paper examines how environmental health problems, in particular asthma, have been addressed from an environmental justice perspective in a low income community of color in Boston. From our perspective, environmentally related diseases and the disparate impact of these illnesses on low income people and people of color are the result of deeply rooted social injustices based on race and class.